Factors influencing e-Business capability: An empirical study on Malaysian SMEs - Mohamed Razi, Mohamed Jalaldeen; Mohammad, Ruhul Amin; Hussin, Husnayati; Suhaimi, Mohd Adam; Kartiwi, Mira (2016)
Nowadays, e-business or doing business online is the trend. The benefits of using the information technology (IT) for business have been elaborated vastly. As a result, not only large scale companies use IT in their business activities, even the SMEs are interested to use it. The Malaysian SMEs are also not exceptional to this situation. However, scientific research on e-business in Malaysian SMEs from owners/managers perspective is limited. Therefore, this study aims to investigate the perceived availability/existence of e-business capability in the Malaysian SMEs retails sector and its predictors from owners/managers perspective. For this purpose, data were collected from 200 Malaysian SMEs owners/managers using a self-administered questionnaire. Descriptive analysis and regression analysis were performed using SPSS 16 to achieve the research objectives. According to the findings, the respondents believe that they possess the e-business capability and the technological factors and the environmental factors are emerging as the predictors. More details analyses were performed to see more insights from the dataset and the findings are reported. Since the SMEs are considered the main backbone of any economy, the findings of this study might help the Malaysian SMEs owners/managers and the policy makers.